2011
DOI: 10.3350/kjhep.2011.17.4.261
|View full text |Cite
|
Sign up to set email alerts
|

Virologic response is not durable after adefovir discontinuation in lamivudine-resistant chronic hepatitis B patients

Abstract: Background/AimsWe investigated the durability of the biochemical and virologic responses after adefovir (ADV) discontinuation in lamivudine-resistant (LMV-R) chronic hepatitis B (CHB) patients, and the outcomes of ADV discontinuation compared to that of ADV maintenance.MethodsThe indication for ADV treatment cessation was an undetectable level of hepatitis B virus (HBV) DNA documented on two occasions at least 6 months apart. All patients received additional ADV for at least 12 months after the confirmation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 25 publications
(31 reference statements)
0
25
0
Order By: Relevance
“…The literature search initially identified 972 papers; of those, 25 fulfilled the inclusion and exclusion criteria for this review (http://onlinelibrary.wiley.com/doi/10.1002/hep.28438/suppinfo). The main characteristics of the included studies and patients are presented in Tables and .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature search initially identified 972 papers; of those, 25 fulfilled the inclusion and exclusion criteria for this review (http://onlinelibrary.wiley.com/doi/10.1002/hep.28438/suppinfo). The main characteristics of the included studies and patients are presented in Tables and .…”
Section: Methodsmentioning
confidence: 99%
“…In total, 2332 (each study contribution from 11 to 401) patients were included in the 25 studies. All but one were cohort studies (three prospective, one retrospective‐prospective, and 20 retrospective, while one was a randomized study comparing the effects of 12 versus 24 months of additional therapy after response to lamivudine in HBeAg‐negative CHB . One study was found to have high quality, 14 to have acceptable quality, and 10 to have low quality based on their risk of bias assessments (http://onlinelibrary.wiley.com/doi/10.1002/hep.28438/suppinfo).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations